1991
DOI: 10.1002/cne.903030210
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and terminating patterns of masseteric neurons of the mesencephalic trigeminal nucleus in the rat: An intracellular horseradish peroxidase labeling study

Abstract: In order to study the morphological characteristics and terminating patterns of the neurons of the trigeminal mesencephalic nucleus (Vme), 55 masseteric neurons in Vme in the rat were stained by intracellular injection of horseradish peroxidase (HRP). Labeled cells were distributed throughout the nucleus. These neurons were divided into three types: uni- or pseudounipolar (type A, n = 43), bipolar (type B, n = 5), and multipolar cells (type C, n = 7). Each type was further divided into two subtypes according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 47 publications
7
54
1
1
Order By: Relevance
“…These results indicate that two morphologically distinct cell populations can be identified in the MeV of duck, rat, and rabbit and that primary sensory cells in the MeV for jaw closing muscles do not send collaterals to the cervical spinal cord. In the light of these findings, the existence of major differences related to MeV among animal species, such as, for instance, rat, rabbit, and cat, as already suggested by Walberg et al (1984) and Luo et al (1991), can be confirmed. With respect to the morphology of the MeV cells related to the jaw closing muscle afferents in particular, discrepancies are noticed between the above-mentioned species.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These results indicate that two morphologically distinct cell populations can be identified in the MeV of duck, rat, and rabbit and that primary sensory cells in the MeV for jaw closing muscles do not send collaterals to the cervical spinal cord. In the light of these findings, the existence of major differences related to MeV among animal species, such as, for instance, rat, rabbit, and cat, as already suggested by Walberg et al (1984) and Luo et al (1991), can be confirmed. With respect to the morphology of the MeV cells related to the jaw closing muscle afferents in particular, discrepancies are noticed between the above-mentioned species.…”
Section: Discussionsupporting
confidence: 67%
“…In the literature, the findings concerning the central projections of the MeV neurons are controversial, since RECORD 249:255-258 (1997) they largely depend on the species studied and methods used (Luo et al, 1991;Raappana and Arvidsson, 1993). The present study, carried out in an avian and two mammalian species, verified, by means of fluorescent retrograde double-labeling technique, the possibility that the MeV neurons that innervate the muscle spindles of the jaw closing muscles could also have collaterals projecting to the cervical level of the spinal cord.…”
mentioning
confidence: 99%
“…The Mes V has other roles including transferring information of vibrissa movements to other central nervous system (CNS) areas [2] as well as regulating feeding and exploratory behavior [3]. According to the morphological characteristics and terminating patterns, three types of neurons could be classified in Mes V: (1) jaw muscle spindle afferent Mes V neurons, (2) periodontal ligament mechanoreceptor afferent Mes V neurons and (3) interneurons [4,5]. However, some investigators think that the small multipolar interneurons are not necessarily Mes V neurons.…”
Section: Introductionmentioning
confidence: 99%
“…As multipolar Mes V neurons may exhibit different properties from pseudounipolar ones, the electrophysiological features reviewed in this paper are mainly referring to common Mes V neurons which receive projections from muscle spindles in the jaw-closing muscles and periodontal mechanoreceptors [6]. Mes V neurons were identified on the basis of their morphological characteristics: a spherical or oval cell body, a large nucleus, a prominent single nucleolus and a pseudounipolar process [5]. The electrophysiological features, reflecting the input-output relation of a single cell, are important for exploring the basic function of a cell within a circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Vp comprises a ventral division and a dorsal division (Vpd), which are cytoarchitectonically different and have been proposed to serve the different functions of relaying and processing of sensory signals from the head, such as tactility and trigeminal proprioception [2][3][4] . Such functions of the Vpd can be supported by the findings that this structure receives direct primary input from intraoral structures and possesses diverse afferent and efferent fiber connections with other brain areas [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%